2015
DOI: 10.15403/jgld.2014.1121.242.ury
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Distinction of Non-Alcoholic Fatty Liver Disease using Urinary Volatile Organic Compound Analysis: Early Results

Abstract: Background & Aims: Non-Alcoholic Fatty Liver Disease (NAFLD) is the commonest cause of chronic liver disease in the western world. Current diagnostic methods including Fibroscan have limitations, thus there is a need for more robust non-invasive screening methods. The gut microbiome is altered in several gastrointestinal and hepatic disorders resulting in altered, unique gut fermentation patterns, detectable by analysis of volatile organic compounds (VOCs) in urine, breath and faeces. We performed a proof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Patient characteristics were similar in the three subgroups, except for sex, with a predominance for female in the UC subgroup, however, previous studies have shown that gender does not affect VOC composition. (23)(24)(25) In conclusion, we observed that faecal VOC analysis by FAIMS could discriminate paediatric de novo IBD patients from healthy controls, with modest accuracy. The apparently high specificity of faecal VOCs compared to faecal calprotectin underlines the potential of this method to serve as a complementary, non-invasive technique in the diagnosis of paediatric IBD, possibly limiting the needed number of endoscopies in a subset of children suspected for IBD.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Patient characteristics were similar in the three subgroups, except for sex, with a predominance for female in the UC subgroup, however, previous studies have shown that gender does not affect VOC composition. (23)(24)(25) In conclusion, we observed that faecal VOC analysis by FAIMS could discriminate paediatric de novo IBD patients from healthy controls, with modest accuracy. The apparently high specificity of faecal VOCs compared to faecal calprotectin underlines the potential of this method to serve as a complementary, non-invasive technique in the diagnosis of paediatric IBD, possibly limiting the needed number of endoscopies in a subset of children suspected for IBD.…”
Section: Discussionmentioning
confidence: 59%
“…The FAIMS data was processed using a well-established pipeline, which has been developed specifically for these types of studies and has previously been reported. [19,23,24] In brief, first a preprocessing step was applied to each run in the form of a 2D wavelet transform (using Daubechies D4 wavelets). This performs two tasks, first as a data compression step and secondly as it can aid in the selection of chemical species by extracting 'peaks', which results in concentrating the chemical information into a small number of wavelet coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has extensively investigated the use of VOCs across a wide range of gastrointestinal and metabolic disorders, principally from urine samples [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It is our opinion that urine represents the most acceptable and user-friendly medium, for both patients and the investigating team.…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted urinary metabolic profiling in small numbers of patients has been explored, 18,19 but its diagnostic ability has not been interrogated in detail. Volatile organic compound generated via the gut microbiome and excreted in the urine have been examined in a very small exploratory pilot study with AUC ROC values of 0.73 (0.45‐0.92) to distinguish advanced disease 20 …”
Section: Discussionmentioning
confidence: 99%